The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.12669/pjms.294.3686
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mobile phone addiction level and sleep quality in university students

Abstract: Objective: To determine the mobile phone addiction level in university students, to examine several associated factors and to evaluate the relation between the addiction level and sleep quality. Methods: The study is a cross-sectional research conducted on the students of the Sakarya University between 01 November 2012 and 01 February 2013. The study group included 576 students. The Problematic Mobile Phone Use Scale was used for evaluating the mobile phone addiction level and the Pittsburgh Sleep Quality Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

29
153
3
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(193 citation statements)
references
References 8 publications
29
153
3
8
Order By: Relevance
“…In addition, Brezing et al (2010) in their review of behavioral addictions in youth alluded to the positive association between depression and problematic internet use in adolescents and college students, where internet use is used as a coping strategy. Likewise, we had similar expectation with regard to the effect of personality type A; once more presumed by findings from earlier studies revealing significant positive association between neurotic personality trait and smartphone addiction in Korean college students (Mok et al, 2014), personality type A and problematic mobile phone use in Turkish university students (Sahin et al, 2013), and type A behavior traits and mobile phone dependence after adjustment for health-related lifestyle habits and depressive state in Japanese medical university students (Masahiro & Satoko, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In addition, Brezing et al (2010) in their review of behavioral addictions in youth alluded to the positive association between depression and problematic internet use in adolescents and college students, where internet use is used as a coping strategy. Likewise, we had similar expectation with regard to the effect of personality type A; once more presumed by findings from earlier studies revealing significant positive association between neurotic personality trait and smartphone addiction in Korean college students (Mok et al, 2014), personality type A and problematic mobile phone use in Turkish university students (Sahin et al, 2013), and type A behavior traits and mobile phone dependence after adjustment for health-related lifestyle habits and depressive state in Japanese medical university students (Masahiro & Satoko, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Our findings from correlation analysis of a significant positive association between younger age at first use and development of smartphone addiction are comparable to those of Orsal et al (2013) and Sahin et al (2013) which revealed significant associations between younger age at first use of internet (≤ 9 vs. 10-12 vs. ≥ 13 years) and higher internet addiction median score, and between younger age at first mobile phone use (≤13 vs. ≥16 years) and higher mobile phone addiction median score in Turkish university students, respectively. However, they were unlike those of Darcin et al (2016) who did not find any significant correlation between earlier age at first smartphone use and smartphone addiction among a sample of Turkish university students.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Even though according to the above-mentioned TUIK, mobile telephone use in Turkey is very high, there are only recent and few studies regarding the problematic use of mobile phones (5,9,(13)(14)(15)(16)(26)(27)(28)(29). For problematic mobile phone use in Turkey, we can find two adapted instruments (26,28) and one scale developed for adolescents (29).…”
mentioning
confidence: 99%